Identifying speech, language and communication needs among children in residential care - Susan McCool; Irene Stevens (Scottish Journal of Residential Child Care)
It is recognised that levels of communication impairment are likely to be higher among looked-after children than they are in the general population (Royal College of Speech and Language Therapists [RCSLT], 2006). Moreover, there are claims that communication needs in this vulnerable population remain largely undetected and unmet (Cross, 2004). Empirical research in this area is lacking.